EIA decision-making and administrative justice: an empirical analysis. Issue 10 (10th June 2022) - Alberts, R.C.; Retief, F.P.; Roos, C.; Cilliers, D. P.; Fischer, T.B.; Arts, J.
Abstract : Environmental impact assessment (EIA) is implemented in most countries as an administrative procedure. In this context, it is subject to the principles of administrative justice. However, to date, no empirical research has been conducted to determine the extent to which EIA decisions comply with the principles of administrative justice. In this paper, empirical data from 42 EIA cases in South Africa are used to establish EIA compliance with the administrative justice principles of lawfulness, procedural fairness and reasonableness. This is achieved by measuring EIA decisions against specially developed key performance indicators (KPIs). Overall, decisions were found to mostly comply with the principles of administrative justice. However, questions arise with regards to the quality and substance of the information feeding into the decision-making process and on which decisions are ultimately based.